2015
DOI: 10.1177/2374289515606730
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Interactive Modeling Tool to Analyze Scenario-Based Physician Workforce Supply and Demand

Abstract: Effective physician workforce management requires that the various organizations comprising the House of Medicine be able to assess their current and future workforce supply. This information has direct relevance to funding of graduate medical education. We describe a dynamic modeling tool that examines how individual factors and practice variables can be used to measure and forecast the supply and demand for existing and new physician services. The system we describe, while built to analyze the pathologist wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The AAMC is developing a modeling tool to improve analytic capabilities with regard to changing physician work patterns, market saturation and displacement of occupations and select specialties, current shortages and inefficiencies, and new care delivery and financing models . The modeling tool that the CAP developed has been useful in evaluating future workforce needs for subspecialties (eg, molecular diagnostics) . Fraher et al currently have the only online tool available for public use.…”
Section: Discussionmentioning
confidence: 99%
“…The AAMC is developing a modeling tool to improve analytic capabilities with regard to changing physician work patterns, market saturation and displacement of occupations and select specialties, current shortages and inefficiencies, and new care delivery and financing models . The modeling tool that the CAP developed has been useful in evaluating future workforce needs for subspecialties (eg, molecular diagnostics) . Fraher et al currently have the only online tool available for public use.…”
Section: Discussionmentioning
confidence: 99%
“…Marshall et al [13] reported recommendations on the potential of dynamic simulation modeling methods to support health care decision-makers evaluating interventions to improve the effectiveness and efficiency of health care delivery. Gupta et al [14] described the steps needed and data required for analysis of supply and demand from a system perspective. They proposed a modeling tool that allows educators and policy makers, in addition to physician specialty organizations, to assess how various factors may affect demand (and supply) of current and emerging health services.…”
Section: Empirical Studies Related To This Researchmentioning
confidence: 99%